2019
DOI: 10.1101/665745
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Bacterial Surface Layer Protein Exploits Multi-step Crystallization for Rapid Self-assembly

Abstract: 24Surface layers (S-layers) are crystalline protein coats surrounding microbial cells. S-layer 25 proteins (SLPs) regulate their extracellular self-assembly by crystallizing when exposed to an 26 environmental trigger. However, molecular mechanisms governing rapid protein crystallization 27 in vivo or in vitro are largely unknown. Here, we demonstrate that the C. crescentus SLP readily 28 crystallizes into sheets in vitro via a calcium-triggered multi-step assembly pathway. This 29 pathway involves two domains… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Within this study and in previous attempts to crystallize RsaA (Bharat et al, 2017), we found that Mg 2+ could not mediate S-layer stabilization or oligomerization. Supplementing M2G medium with an excess of MgSO 4 to compensate for the exclusion of CaCl 2 resulted in non-fluorescent cells (Figure 1F), suggesting improper S-layer assembly or S-layer shedding, which is in agreement with previous biochemical reports (Herrmann et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Within this study and in previous attempts to crystallize RsaA (Bharat et al, 2017), we found that Mg 2+ could not mediate S-layer stabilization or oligomerization. Supplementing M2G medium with an excess of MgSO 4 to compensate for the exclusion of CaCl 2 resulted in non-fluorescent cells (Figure 1F), suggesting improper S-layer assembly or S-layer shedding, which is in agreement with previous biochemical reports (Herrmann et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…When no additional CaCl 2 was added to the medium (Figure 1E), the resulting cell fluorescence readings were indistinguishable from unlabeled control cells (Figure 1G) and drastically lower than cell fluorescence intensities seen in cells in 500 or 250 mM CaCl 2 . These observations support the hypothesis that the formation of a viable S-layer is strongly dependent on the concentration of Ca 2+ in the growth medium and shows that even a small reduction in the available CaCl 2 can significantly affect the retention and display of the S-layer on cells, in agreement with other reports (Herrmann et al, 2020). To probe the Mg 2+ dependence of S-layer assembly, we included a sample of C. crescentus cells grown in M2G containing 0 mM CaCl 2 and 1,000 mM MgSO 4 (Figure 1F).…”
Section: Ca 2+ Ions Are Critical For the Retention And Display Of The Caulobacter Crescentus S-layer On Cellssupporting
confidence: 93%
See 3 more Smart Citations